2018
DOI: 10.18616/is.v7i1.4260
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes Da Obesidade Em Crianças Acompanhadas Por Uma Entidade De Assistência Social Em Itabuna- Ba

Abstract: A obesidade infantil apresentou um considerável aumento nas últimas décadas, constituindo-se como uma verdadeira pandemia. Trata-se de um quadro preocupante, pois é uma pré-disposição para o desenvolvimento de doenças como a hipertensão, diabetes mellitus tipo 2, doenças cardiovasculares, entre outras. Dado isso buscou-se destacar a importância da qualidade de vida na prevenção da obesidade em menores assistidos por uma entidade de assistência social na cidade de Itabuna-BA, e especificamente identificar o índ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In relation to practicing physical activity, a research study conducted in Piauí with adolescents aged between 13 and 19 years old identified that the level of physical activity characterized as active was 12.6% 26 , lower than that found in this study. It is believed that the increasingly frequent practice of sedentary leisure and the fast technological development of the past few years, characterized by the increased time spent on electronic games, computers, television and cellphones, reduce the adolescents' interest in activities that provide energy expenditure 2,27 . It is important to highlight that the practice of physical activity among adolescents implies the improvement of general well-being, mental health and prevention of chronic non-communicable diseases, with governmental measures and of the society as a whole being indispensable to prevent sedentary lifestyle in the young population 2 .…”
Section: /13mentioning
confidence: 99%
“…In relation to practicing physical activity, a research study conducted in Piauí with adolescents aged between 13 and 19 years old identified that the level of physical activity characterized as active was 12.6% 26 , lower than that found in this study. It is believed that the increasingly frequent practice of sedentary leisure and the fast technological development of the past few years, characterized by the increased time spent on electronic games, computers, television and cellphones, reduce the adolescents' interest in activities that provide energy expenditure 2,27 . It is important to highlight that the practice of physical activity among adolescents implies the improvement of general well-being, mental health and prevention of chronic non-communicable diseases, with governmental measures and of the society as a whole being indispensable to prevent sedentary lifestyle in the young population 2 .…”
Section: /13mentioning
confidence: 99%